Postoperative spinal orthosis may not be necessary for minimally invasive lumbar spine fusion surgery: a prospective randomized controlled trial - Hsuan-Hsiao Ma; Pei-Hsi Wu; Yu-Cheng Yao; Po-Hsin Chou; Hsi-Hsien Lin; Shih-Tien Wang; Ming-Chau Chang (BMC Musculoskeletal Disorders, 2021)
Abstract Background With the progress and success in minimally invasive surgery of transforaminal lumbar interbody fusion (MIS TLIF), the musculoskeletal injury was minimized. However, the role of postoperative orthosis in MIS TLIF has not been established and there is little evidence supporting the routine use of orthosis in MIS TLIF. Methods This is a prospective randomized clinical study. 90 patients who underwent MIS TLIF were randomly divided into groups A (with postoperative spinal orthosis) and B (without postoperative spinal orthosis). Patients were followed up for an average of 12.6 months. Clinical outcome was assessed using the Oswestry disability index (ODI) and visual analogue scale (VAS). Fusion rate was classified with the BSF scale system at postoperative 6-month, and 12-month. Results Both groups had similar patient demographics. The use of postoperative spinal orthosis had no significant influence on instrumentation-related complications or radiological parameters at each follow-up. Conclusions In this study, we conclude that postoperative spinal orthosis is not necessary for MIS TLIF. Patients without postoperative spinal orthosis had the same fusion rates and improvement of VAS and ODI scores.